PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH DAN KONEKSI MATEMATIKA SISWA SMP DENGAN MENGGUNAKAN PEMBELAJARAN BERBASIS MASALAH - Leni Agustina Daulay (Study Program of Mathematics Education of Unimed Postgraduate Program, 2009)
The purposes of this study are to examine: (1) Increasing mathematical problem-solving abilities of students who obtained a model of problem-based learning better than students who received direct instruction model, (2) Increasing the ability of students who obtained a mathematical connection problem based learning model is better than students who received direct instruction model, (3) Levels of student activity during problem-based learning process in progress. This research is a semi-experimental. The population of this research is of seventh grade of Juinor High School accredited B at Tebing Tinggi. At random, one school was chosen as research subjects, namely Junior High School District 4 at Tebing Tinggi. Two Classes of seventh grade were selected randomly. Class experiment treated the problem based learning model and classroom teaching model treated controls directly. The instrument used consisted of: a test of mathematics problem-solving ability, mathematical ability test connection and observation sheet.Data analysis was performed with analysis of covariance (ANACOVA). The result of this study is the overall student learning with problem-based learning is significantly better in improving mathematical problem solving skills and connections that learning mathematics than students with hands-on teaching and activities of students in problem-based learning is effective. Based on the results of the study, the researchers recommend that: (1) problem-based learning in mathematics learning that emphasizes problem solving skills and mathematical connections students can be used as an alternative for implementing innovative math learning.